Active-Network with Passive Capacitor based High Gain DC-DC Converter - Singh A.; Siva V.; Singh S.K.; Kumar A. (My University, 2025)
High voltage gain converter is used in various applications, like solar panel energy systems, fuel-cell energy conversion system. This manuscript presents a transformerless high voltage gain dc-dc converter. It utilizes the concept of active switched-inductor (ASL) and Passive switched-capacitor (PSC). The proposed structure interconnects energy storing elements-inductor and capacitor, active power switch and diode in a specific way to obtain high voltage gain. Design methodology, operating principle, device stress and effect of load current on voltage gain are analyzed here. Moreover, controller is designed using Ziegler-Nicholas frequency domain method. In order to verify the theoretical concept steady state analysis and MATLAB simulation is performed. Finally, laboratory prototype is built and tested. © 2022 IEEE